Development of reconfigurable rehabilitation robot for post-stroke forearm and wrist training - Khor, Kang Xiang (Penerbit UTM Press, 2015)
Rehabilitation robots are gradually becoming popular for stroke rehabilitation to improve motor recovery, as robotic technology can assist, enhance, and further quantify rehabilitation training for stroke patients. However, most of the available rehabilitation robots are complex and involve multiple Degrees-Of-Freedoms (DOFs) causing it to be very expensive and huge in size. Rehabilitation robot needed to be useful but also should be cost-effective to be able to use in current rehabilitation process. This paper present the design of reconfigurable rehabilitation robot that able to adopt different training movement by changing the configuration of the device. The developed robotic system able to perform training for wrist, forearm and other functional rehabilitation training by using suitable modular units. Preliminary study with three stroke subject were presented to evaluate the functionality in different training modes for forearm and wrist rehabilitation training.